Social Media Leveraging For Industrial E-Recruitment: A Study Of PT. Boga Inti - Steven Brian Kenneth Hutomo; Idfi Setyaningrum; Mintarti Ariani; Joshi Maharani Wibowo (Jurnal Ekuilnomi, 2024)
This research aims to determine how PT Boga Inti implements the e-recruitment process in recruiting human resources. The findings are anticipated to offer insights into the execution of this online recruitment for industrial company, highlight the availability of qualified candidates, and foster the development of a more effective and efficient management recruitment process both for employer and employee. This study use qualitative approach based on a case study to capture the problem residing on e-recruitment activity. Data collection was carried out by observation and interviews, based on purposive sampling, in accordance with the purposes of study. The findings show that PT Boga Inti faces challenges in filtering job applicants and finding candidates that match the required criteria due to three obstacle: 1) A lot of candidates that is not match with company requirement, 2) Salary offers is too low in some region, 3) Uneven recruitment information distribution. To overcome the problem, these studies develop a few strategies to support the needs of object study, through the uses of paid promotion, Instagram - Ads, and job vacancy websites or social media accounts